La literatura y el cine como espacios de resistencia al paradigma héteronormativo - Melo, Adrián (2011)
This writing presents cinema and literary discourse as fields where not only\ndominant categories are questioned, but also, alternatives to the heteronormative paradigm\ncreated by psychoanalysis, law and other sciences, are suggested. The authors\nput forward that the gaucho, while archetypical figure of virility and national being,\nalso allows for the modern notion of masculinity to be subverted. After a brief genealogy\nof this concept in national literature, the writing concludes with a detailed analysis\nof the gaucho character in Martín Fierro, La Vuelta de Martín Fierro, Don Segundo\nSombra and Vidalita